Deterring Drivers: A Process Evaluation of an Initiative to Reduce Car Theft and Joyriding by First Nations Young People - Dodd, Shannon (Journal of contemporary criminal justice, 2025)
Joyriding is a dangerous, illegal activity primarily involving young males from disadvantaged backgrounds. In Australia, First Nations youth are disproportionately represented in unlawful use of motor vehicle offenses. This study evaluates the “Deterring Drivers” program, which aims to reduce car theft and joyriding through group-based education and recreational activities. Data from participant observation and interviews highlight the program’s effectiveness in fostering social connections within a culturally safe environment, enhancing social cohesion, and promoting empathy for crime victims. In addition, the study underscores the importance of providing legal and constructive avenues for young people’s interest in cars, potentially steering them away from crime by offering training and employment opportunities.